2013
DOI: 10.1002/ana.23940
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 defense pathway: Experimental evidence for its protective role in epilepsy

Abstract: These findings extend the potential of Nrf2-based therapies to epilepsy and add to the rapidly accumulating evidence from other neurodegenerative and inflammatory disease models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 44 publications
3
115
0
1
Order By: Relevance
“…Likewise in the liver, nuclear extracts demonstrated increased Nrf2 expression after 1 and 3 weeks on the diet, accompanied by elevations in both NAD(P)H:quinone oxidoreductase activity and the expression of Nrf2 target heme oxygenase-1 after 3 weeks on the diet ( 97 ). Interestingly, a recent study found that increasing Nrf2 expression in a rat model of temporal lobe epilepsy decreased spontaneous seizures ( 100 ).…”
Section: Bioenergetic and Mitochondrial Changesmentioning
confidence: 98%
“…Likewise in the liver, nuclear extracts demonstrated increased Nrf2 expression after 1 and 3 weeks on the diet, accompanied by elevations in both NAD(P)H:quinone oxidoreductase activity and the expression of Nrf2 target heme oxygenase-1 after 3 weeks on the diet ( 97 ). Interestingly, a recent study found that increasing Nrf2 expression in a rat model of temporal lobe epilepsy decreased spontaneous seizures ( 100 ).…”
Section: Bioenergetic and Mitochondrial Changesmentioning
confidence: 98%
“…Systems biology-based approaches of network pharmacology have recently been proposed for developing antiepileptic and antiepileptogenic treatments [4,50,51]. In addition to combining drugs in network pharmacology, one target that modulates several pathways is an alternative option as illustrated by the mTOR pathway [52] or transcription factors such as Nrf2 [53].…”
Section: Concept Of Network Pharmacologymentioning
confidence: 99%
“…Both groups of antioxidant genes have been proposed as therapeutic candidates, e.g., for neurodegenerative disorders, diabetic complications, and cardiovascular diseases, with the hope that the enzymes would be more specific, generating fewer side effects than chemical antioxidants, and that the TFs would provide a broad defense by activating hundreds of genes (15)(16)(17). However, only a few studies have been conducted to test this therapeutic strategy by gene delivery via viral vectors in animal models in vivo (18)(19)(20)(21)(22)(23)(24)(25), and no studies have compared the effectiveness of the enzymes versus the TFs, or NRF2 versus PGC1a.…”
Section: Introductionmentioning
confidence: 99%